Managing change resistance among employees - Nur Amirah , Roslan (2013)
Change resistance among employees is a common phenomenon that can’t be avoid in any industry. Most of the employees, against organizational change because of many reasons. Some of the reasons are misunderstanding about the change, feeling uncertain with the change result, feel that the organizational change can threaten their status quo, hard to adapt with any changes, not ready to face change process, and dislike the change. In order to handle this resistance problem, management need to practice a good approach, so that, the employees will not continuously against the change. There are six situational approaches that can be practice by management in order to solve this problem. The six approaches are as follow; (1) education and communication approach, (2) participation and involvement approach, (3) facilitation and support approach, (4) negotiation and agreement approach, (5) manipulation and cooptation approach, and the last one is (6) explicit and implicit coercion approach.